Towards Promoting the Culture of Sharing: Using Blockchain and Artificial Intelligence in an Open Science Platform. - Denden, Mouna; Abed, Mourad (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
Several studies in the literature have proposed the use of artificial intelligence (AI) tools to manage big data and further enhance collaboration between researchers on open science platforms, hence promoting the culture of safely sharing reliable data. Moreover, some other studies further proposed the use of blockchain technology to secure data, provide transparency in data analysis, and also keep track of all collaborations within open science platforms. Despite the importance of AI and blockchain technology in open science platforms, no study, to the best of our knowledge, has implemented and discussed the benefits of using both technologies together or how blockchain can enhance AI systems in open science. Therefore, to address this research gap, this study presents a newly developed open science platform that harnesses the power of AI and blockchain technologies to promote and foster a culture of sharing and seamless collaboration among universities worldwide. This platform was then validated through focus group analysis from the European University for Customised Education (EUNICE) partners, which is the project context of this present study. The findings revealed that the use of AI and blockchain enabled researchers and institutions to share open science more effectively. Specifically, the use of AI features in Open REUNICE enhanced data management processes, particularly by improving metadata accuracy, searchability and reusability, thereby addressing critical needs in research workflows. Additionally, the use of Blockchain was found to play a critical role in addressing legal challenges and enhancing user trust.